Osteocyte Egln1/Phd2 links oxygen sensing and biomineralization via FGF23 - Megan L. Noonan; Pu Ni; Emmanuel Solis; Yamil G. Marambio; Rafiou Agoro; Xiaona Chu; Yue Wang; Hongyu Gao; Xiaoling Xuei; Erica L. Clinkenbeard; Guanglong Jiang; Sheng Liu; et al. (Bone Research, 2023)
Abstract Osteocytes act within a hypoxic environment to control key steps in bone formation. FGF23, a critical phosphate-regulating hormone, is stimulated by low oxygen/iron in acute and chronic diseases, however the molecular mechanisms directing this process remain unclear. Our goal was to identify the osteocyte factors responsible for FGF23 production driven by changes in oxygen/iron utilization. Hypoxia-inducible factor-prolyl hydroxylase inhibitors (HIF-PHI) which stabilize HIF transcription factors, increased Fgf23 in normal mice, as well as in osteocyte-like cells; in mice with conditional osteocyte Fgf23 deletion, circulating iFGF23 was suppressed. An inducible MSC cell line (‘MPC2’) underwent FG-4592 treatment and ATACseq/RNAseq, and demonstrated that differentiated osteocytes significantly increased HIF genomic accessibility versus progenitor cells. Integrative genomics also revealed increased prolyl hydroxylase Egln1 (Phd2) chromatin accessibility and expression, which was positively associated with osteocyte differentiation. In mice with chronic kidney disease (CKD), Phd1-3 enzymes were suppressed, consistent with FGF23 upregulation in this model. Conditional loss of Phd2 from osteocytes in vivo resulted in upregulated Fgf23, in line with our findings that the MPC2 cell line lacking Phd2 (CRISPR Phd2-KO cells) constitutively activated Fgf23 that was abolished by HIF1α blockade. In vitro, Phd2-KO cells lost iron-mediated suppression of Fgf23 and this activity was not compensated for by Phd1 or −3. In sum, osteocytes become adapted to oxygen/iron sensing during differentiation and are directly sensitive to bioavailable iron. Further, Phd2 is a critical mediator of osteocyte FGF23 production, thus our collective studies may provide new therapeutic targets for skeletal diseases involving disturbed oxygen/iron sensing.